ANALISIS RISIKO PASCA PANEN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT DI KABUPATEN DHARMASRAYA - . Yulistriani; Cindy Paloma; . Hasnah (LPPM Universitas Malikussaleh – Indonesia, 2018)
One of the risks often faced by palm oil agribusiness is the post harvest risk of losing fresh fruit bunches (FFB) from each post-harvest chain (loss post-harvest). Palm oil which is a mainstay of plantation crops Dharmasraya region, its production from year to year is always the largest compared with other commodities. However, in 2015 palm oil production was decrease compared to the previous year. This study aims to analyze farmers' management capability in palm oil management, analyze the large loss of FFB yields in each chain from farmer (harvest) to final processing plant, analyze the probability and impact of post-harvest loss FFB and post-harvest post-harvest status in each post-harvest chain (stage). The large percentage of production losses to the total production of FFB produced is 3.85% for the land, 0.05% for the process of crude FFB checking (TPH), and 5.5% in the factory sorting (PKS). The impact of losses resulting from post-harvest loss of FFB in total per hectare of land is Rp 2,848,528,41 at factory sorting, and is the biggest loss compared to other chains.